A qualitative content analysis of the experience of living with hypospadias: varying impact on identity and interpersonal relationships - Phillips, Lottie; Dennermalm, Nicklas; Örtqvist, Lisa; Engberg, Hedvig; Holmdahl, Gundela; Fossum, Magdalena; Möller, Anders; Nordenskjöld, Agneta (Frontiers in Pediatrics, 2024)
Objectives: There is a lack of in-depth studies on men’s personal experiences of having hypospadias across different aspects of their lives. We therefore aimed to explore the experience of having hypospadias in relation to identity and interpersonal relationships. Subjects and methods: Using purposive sampling, we included 17 adult men aged 20-49 with variation in hypospadias phenotype. The informants further represented variation in sexuality, relationship status, parental status, and familial cultural context. In-depth interviews were conducted with each informant and the data was analysed using qualitative content analysis. Results: We identified four categories. Firstly, The internal experience of hypospadias in relation to being different, being impacted, and being masculine. The remaining three categories related to interpersonal spaces: Intimate spaces, comprising personal relationship with sex, having sex, and being in a relationship; Familial spaces, comprising being a son, and becoming a father; and Public spaces, comprising being hidden, being naked, and peeing. We identified the latent theme varying impact and coping, highlighting differences in experiences relating to both the internal and interpersonal. Discussion: Issues related to hypospadias included struggles with identity and confidence, as well as recurring patterns of social and sexual avoidance. While informants generally related to certain shared experiences, there is large variation in how much hypospadias impacts life, ranging from hardly at all to extensively. This could also fluctuate over time, with puberty and adolescence being an especially sensitive period. Functional and aesthetic outcomes are potentially important for well-being, especially in the case of more severe complications, while personal and interpersonal circumstances play a role in coping and the overall experience of the individual. Conclusion: Healthcare, research, and other channels such as patient groups may be able to offer support to those who need it to help more boys and men with hypospadias live unhindered lives.